An Empirical Method of Assessing Topic Familiarity in Reading Comprehension Research - Spyridakis, Jan H.; Wenger, Michael J. (British educational research journal, 1991)
While numerous studies have shown that prior knowledge and topic familiarity affect comprehension and usability of a text, few researchers account for readers' topic familiarity in studies that investigate other reading comprehension variables. This research note briefly reviews the literature on the effect of prior knowledge and text familiarity on document comprehension and usability and discusses current methods for assessing subjects' topic familiarity. An empirically based method for effectively assessing subjects' topic familiarity is presented.